(untitled) (Ameghiniana, 2022)
The early diversification of caimanines is one of the least understood aspects of the evolutionary history of Crocodylia. The Palaeogene Argentinian caimanine record is extremely relevant because it provides key information on the early history of the clade. Most of the Palaeocene South American species are only or mainly known from partial lower jaws. Among the oldest Argentinian caimanines, Notocaiman stromeri (middle Palaeocene, Las Violetas Formation, Chubut Province) and Eocaiman palaeocenicus (lower Palaeocene, Salamanca Formation, Chubut Province) are represented by a partial left dentary and a fairly complete lower jaw, respectively. Notocaiman stromeri, described in 1937, has been phylogenetically interpreted from an alligatorid closely related to Eocaiman to an indeterminate eusuchian, but a modern anatomical revision of this species is lacking. Here, we redescribe in detail the only known specimen of Notocaiman stromeri with the aim of revising its taxonomy and phylogenetic relationships. We found that Notocaiman stromeri cannot be differentiated from Eocaiman palaeocenicus, but it can be distinguished from all other crocodylians. Our phylogenetic analyses found Notocaiman stromeri as the sister taxon to the Eocaiman cavernensis + Eocaiman itaboraiensis clade. Thus, here we consider Notocaiman stromeri a subjective senior synonym of ‘Eocaiman palaeocenicus’, but we keep Notocaiman as a valid genus because only one additional step breaks the monophyly of the Notocaiman + Eocaiman clade. Our revision reduces the alpha taxonomic diversity of alligatorids in the Palaeogene of South America, but reinforces a geographically broad diversification of the Notocaiman + Eocaiman clade from the Palaeocene to the Eocene/Miocene in this continent.